China Responsibility in Case of Covid 19 Pandemic Under International Law - Hilton Tarnama Putra M; Jarkasi Anwar (Nurani Hukum, 2021)
Pandemic COVID-19 was start from Wuhan, China then spread to the rest of the world. Under international law of public health, states have obligations to cooperate in tackling international health emergency. WHO Constitution and IHR confirms those obligations in which state denied its will arise state responsibility. The purpose of this research is to elaborate state obligations under international law to handle COVID-19 and particularly to China. This research use normative legal research method which means to analysis international law norm in practice. The results of this research are, first there are several obligations to state in handle COVID-19 such as to cooperate, to notify WHO and to made domestic regulation. Second, China is not responsible for COVID-19 case because China did not breach any international obligations under international law.